Studies on Swelling Kinetics and Temperature-Sensitive Superabsorbent Hydrogels Based on Carboxymethylcelloluse - Sadeghi, Mohammad; Safari, Soudeh; Gudarzi, Anahita; Shahsavari, Hadis; Sadeghi, Hossein (Asian Journal of Chemistry, 2013)
To develop materials with improved controllability and specificity, we have investigated swelling kinetics and temperature-sensitive properties using thermal cross-linking of a superabsorbing hydrogel based on carboxymethylcellulose and N-isopropylacrylamide and methacrylamide in a homogeneous solution. The hydrogels exhibited tem-sensitivity and cation exchange properties. The temperature and pH-reversibility properties of the hydrogels make the smart polymers as good candidates for considering as potential carriers for bioactive agents, e.g., drugs. The swelling variations of hydrogels were also explained according to swelling theory based on the hydrogel chemical structure.